Safeguarding Privacy, Ensuring Ethics: Exploring Implications of Data-Driven Workforce Planning in State Universities and Colleges - Baluis, Ichelle F. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Organizations such as State Universities and Colleges (SUCs) recognize the critical importance of data-driven decision-making. Despite the promising benefits of data-driven decision-making, there are unavoidable ethical issues and privacy risks associated with access to workforce data. However, these risks have been limitedly researched particularly in the context of Higher Education Institutions (HEIs) such as SUCs. In line with this, this study sought to explore the implications of data-driven workforce planning in the context of SUCs. The researcher adopted the mixed method approach where a survey was conducted to ten (10) HRMO/HRDO in various SUCs in the Philippines. The survey aims to gather both qualitative and quantitative data regarding perceptions, and experiences towards data-driven workforce planning. The results showed that information on offered academic programs, faculty-student ratios, retirement and attrition rates, needs for skills and expertise, and enrolment projections can help predict and meet the demand for workforce in SUCs in a more accurate and tailored manner. With these data, SUCs perceived that Data Privacy and Consent, Anonymity and Confidentiality, and Consistency with Legal Requirements are among the top ethical considerations in data-driven workforce planning. Likewise, the Misinterpretation of Data, Privacy Violations, Data Security Breaches, and Legal and Regulatory Consequences, emerged as the top ethical dilemmas and data privacy implications. Therefore, SUCs need to establish policies taking into consideration the findings of this study to achieve the right balance between harnessing employee data for planning purposes and upholding ethical standards while ensuring strong data privacy controls.